The failure of supervisory stress testing: Fannie Mae, Freddie Mac, and OFHEO - W. Scott Frame; Kristopher Gerardi; Paul S. Willen (Federal Reserve Bank of Boston, 2015)
In the aftermath of the global financial crisis, policymakers in the United States and elsewhere have adopted stress testing as a central tool for supervising large, complex, financial institutions and promoting financial stability. Although supervisory stress testing may confer substantial benefits, such tests are vulnerable to model risk. This paper studies the risk-based capital stress test conducted by the Office of Federal Housing Enterprise Oversight (OFHEO) for Fannie Mae and Freddie Mac, the two government-sponsored enterprises (GSEs) that are central to the U.S. housing finance system. This research aims to identify the sources of the stress test's spectacular failure to detect the growing risk and ultimate financial distress at these GSEs as mortgage market conditions deteriorated in 2007 and 2008. The analysis focuses on a key element of OFHEO's stress test, the models used to predict default and prepayment of 30-year fixed-rate mortgages.
Keywords: G21; G23; G28; 330; bank supervision; stress test; model risk; residential mortgages; government-sponsored enterprises